The adhesion phenomena in polypropylene/wollastonite composites - Švab, Iztok (Acta chimica slovenica, 2005)
Modification of polypropylene (PP) with wollastonite fillers was investigated in this paper. Three types of different silane pretreated wollastonite mineral filler were used for preparation of binary PP/wollastonite composites. The composite samples were homogenized in a Brabender Plasti-Corder kneading chamber and compression moulded into plates on a laboratory press. The adhesion between the wollastonite fillers used in this study and the PP matrix was predicted on the basis of the calculated adhesion parameters (work of adhesion, interfacial free energy and spreading coefficient) obtained by the surface free energy of pure materials. The contact angle method was used to determine surface free energy of components. The obtained values of adhesion parameters at the interface in the composites were correlated with mechanical properties as well as morphology observations of corresponding composites and were proved to be in relatively good agreement with the mechanical property measurements. Stronger adhesion in investigated composites has reflected in higher yield stress and tensile strength at break but in lower elongation at break and impact resistance.
Keywords: mehanske lastnosti; morfologija; polipropilen; wollastonit